1995
DOI: 10.11150/kansenshogakuzasshi1970.69.864
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clarithromycin on Macrophage Functions

Abstract: Recently, it has been suggested that macrolide antibiotics act as immunomodulators. In this study, we evaluated the effect of clarithromycin (CAM) on macrophage function. We used the mouse macrophage cell line, J774.1. The following direct effects of CAM on macrophage function were evaluated: chemotaxis to CAM, chemokinetic effect of CAM, and the effect of CAM on macrophage growth. In order to examine the indirect effects of CAM on macrophage functions, we preincubated macrophages with several concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…The literature is controversial regarding the action of clarithromycin on the neutrophilic phagocytosis. While a report observed a decreased phagocytosis associated to the drug (Wenisch et al, 1996), other studies reported an increased activity (Roszkowski et al, 1990;Scaglione et al, 1993;Xu et al, 1995). Differences in methodology, the animal and human models used, the concentrations of the drug in vivo and in vitro, the protocols, and dosage and administration may partially explain the differences reported by these studies (Labro, 2000).…”
Section: Discussioncontrasting
confidence: 52%
“…The literature is controversial regarding the action of clarithromycin on the neutrophilic phagocytosis. While a report observed a decreased phagocytosis associated to the drug (Wenisch et al, 1996), other studies reported an increased activity (Roszkowski et al, 1990;Scaglione et al, 1993;Xu et al, 1995). Differences in methodology, the animal and human models used, the concentrations of the drug in vivo and in vitro, the protocols, and dosage and administration may partially explain the differences reported by these studies (Labro, 2000).…”
Section: Discussioncontrasting
confidence: 52%
“…The remaining MHC class II-positive cells were probably macrophages, based on their morphology [11]. It has been reported that CAM directly stimulates macrophage functions, such as phagocytosis, which were decreased after endotoxin exposure [25]. The number of dermal macrophages and mast cells in dexamethasonetreated mice was numerous at 9 weeks, which may be due to the particularly low sensitivity to steroids [11].…”
Section: Discussionmentioning
confidence: 96%
“…Woo et al 20 recently demonstrated that CRTM suppressed both the systemic and local inflammatory response following surgical trauma, in part, by suppressing monocytosis. Xu et al 17 on the other hand, reported that CRTM dose-dependently stimulated the growth of J744.1 macrophages, in addition to increasing their phagocytic, chemotactic, and cytolytic activity. Increased monocyte phagocytic activity and intracellular killing has also been demonstrated in human patients that were receiving CRTM therapy to treat chronic bronchitis 4 .…”
Section: Discussionmentioning
confidence: 97%
“…Murine studies conducted by Takeshita et al 16 showed that CTRM significantly reduced IL-1 production by peritoneal macrophages, IL-1-induced thymocyte proliferation, and the transformation of splenic lymphocytes. More recently, CRTM was reported to enhance macrophage phagocytosis, chemotaxis and cytolytic activity using the murine macrophage cell line, J774.1 17 .…”
Section: Discussionmentioning
confidence: 99%